Declining Earnings Inequality, Rising Income Inequality: What Explains Discordant Inequality Trends in the United States? - Lukas Lehner; Zachary Parolin; Nathan Wilmers (Institute of Labor Economics (IZA), 2024)
From 2010 to 2019, personal earnings inequality declined in the United States (U.S.) for the first time in decades, yet household income inequality continued to increase. Discordance between trends in personal earnings inequality and household income inequality was greater than in any other decade in recent U.S. history. We introduce a framework to decompose differences in inequality trends. We find that 46% of the 2010-2019 discordance is due to the changing household composition of workers. Specifically, a larger share of young workers are living with their parents, thus combining low personal earnings with high household incomes. The remaining 54% of discordance stems from inequality-increasing shifts in non-labor income (private income, taxes, and transfers). Despite the rare decline in U.S. earnings inequality, household income inequality increased due to changes in workers' household composition, increases in private income among higher-earning households, and the declining redistributive effect of government income transfers.
Keywords: D31; E01; H24; I38; J31; 330; earnings inequality; income inequality; household composition; secondary earners; government transfers